Use of Rice Straw and Black Gram Straw in Fodder Based Goat’s Diets in the Hills of Nepal - Upreti, Chet R.; Kuwar, Bahadur S.; Panday, Shambhu. B. (Nepal Agriculture Research Journal, 2014)
The aim of this study was to investigate the possible use of crop residue such as rice straw and black gram straw (Kushauro) in hill goats’ diet. Twenty male and female goats of age 6- 9 months were divided into 4 dietary groups. Animal of first diet groups (D1) were fed with fodder leaves (Khanyu) only, second diet group (D2) with 20% rice straw + fodder tree foliage, third diet group (D3) with 20% rice straw + fodder tree foliage + concentrate @ 1% of body weight, and fourth diet group (D4) fodder tree foliage + 15% rice straw + 5% black gram straw + concentrate @ 1% of body weight meet to the daily requirement. These rations were fed to animals of individual diet group for 150 days. Daily feed intake, daily weight change was recorded. Body weight was taken at the beginning of the experiment, at the end of experiment and 15 days interval. The result showed that there was significant difference (P <0.05) between different dietary groups for average daily gain (ADG). The highest ADG was observed in D3 (19.6±4.33), followed by D2 (12.67±1.38 g/d) and D4 (11.73±1.78 g/d). The lowest ADG was found in D1 (10.8±1.87 g/d). The result indicated that 20% rice straw can be used in goat diet with supplementary diet of concentrate @ 1% of body weight, and foliage of Khanyu as a basal diet. Feeding only fodder tree foliage is not suitable to get higher ADG in stall-feeding management. Nepal Agric. Res. J. Vol. 8, 2007, pp. 82-87 DOI: http://dx.doi.org/10.3126/narj.v8i0.11595